Why Digital Capabilities Alone Don’t Drive SME Performance: The Mediating Role of Process Innovation in Retail SMEs - Nurul Binti Samsuden; Alhamzah F. Abbas; Nor Amira Syairah Zulkarnain; Wai Chuen Poon; Ummu Ajrah Abdul Rauf (Journal of Applied Engineering and Technological Science (JAETS), 2026)
This study explores the role of digital capabilities (DC) in enhancing the business performance (BP) of retail SMEs in Johor, Malaysia, with a particular focus on the mediating effect of process innovation (PI) and the moderating role of competition intensity (CI). Despite the rising relevance of digital transformation, retail SMEs in Johor, Malaysia, continue to face structural constraints, including limited technological readiness, skill shortages, and intensified competitive pressures. Using primary data from 371 retail SMEs, this study employs Partial Least Squares Structural Equation Modelling (PLS-SEM) to test a multidimensional model grounded in the Resource-Based View (RBV) and Dynamic Capabilities Theory (DCT). The findings reveal that while DC do not exert a direct influence on BP, they significantly enhance PI, which in turn fully mediates the impact on performance. CI does not significantly moderate the relationship between DC and business outcomes. These results suggest that the BP benefits of DC are only realised through innovation-enabling mechanisms rather than direct technological adoption. The study underscores the importance of investing in internal innovation processes and strategic integration to translate digital potential into sustained competitive advantage within the retail SME context.